PENGARUH UJARAN KEBENCIAN PENGGUNA DETIKFORUM TERHADAP KREDIBILITAS MEDIA DETIKCOM - Istifany, Salsa Bila; Kusuma, Satria Kusuma (Universitas Muhammadiyah Jakarta, 2024)
Online media innovates by facilitating discussion forums to enable users with similar interests to interact, fostering a relationship with readers. However, hate speech disseminated by users in discussion forums can affect the credibility of the media itself. Detikforum is a platform created by Detikcom to allow users/readers to discuss certain issues and create various topics. Detikcom aims to engage readers in discussing the latest news and provides a space for expressing thoughts or comments on existing news. This study aims to determine whether hate speech by DetikForum users influences the credibility of Detikcom media. The research employs theories of hate speech and media credibility, using a causal quantitative approach. Data were collected through online questionnaires distributed to respondents using purposive sampling, with 100 respondents meeting the criteria as research samples. The respondents were DetikForum users aware of hate speech cases and who interacted with celebrity tweets addressing hate speech in DetikForum. The study results indicate that hate speech by DetikForum users has a 30.6% impact on the credibility of Detikcom media. The media needs to take firm steps to eliminate hate speech in discussion forums, such as enhancing content moderation through intelligent algorithms and active moderator teams, implementing clear and strict policies on ethical violations, and educating the public on digital literacy and the legal consequences of hate speech. These actions can help the media improve its image and credibility in the public eye while creating a healthy and constructive discussion space.